ANALISIS PENGARUH PELATIHAN DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PADA PT. BANK CAPITAL INDONESIA TBK JAKARTA - Slamet Sutrisno (Jurnal Manajemen Bisnis Krisnadwipayana, 2016)
The research objective to be achieved is to determine the effect of training and leadership to employees performance in PT Bank Capital Indonesia, Tbk Jakarta. The research method used was the regression analysis, correlation and hypothesis testing. Results of this research is no effect either jointly or individually, and leadership training to employees performance in PT Bank Capital Indonesia, Tbk Jakarta. Conclusions: 1). There are influences together training and leadership to employees performance. 2). There is an effect alone training to employees performance . 3). No influence their own leadership to employees performance.